PTH-078 Vedolizumab post resection for Crohn's disease: a 4 year real world experience. (June 2019) - Brooks, Johanne; Tremelling, Mark
Abstract : Introduction: Vedolizumab is a gut specific anti integrin biologic therapy that NICE guidance indicates can only be used only in moderate to severe Crohns disease if an anti-TNF has failed, cannot be tolerated or is contraindicated and should be given as a planned course of treatment until it stops working or surgery is needed. There is no documentation regarding vedolizumab post resectional surgery. This audit utilises 4 years of data of using vedolizumab in a tertiary centre and assesses response rates, the use of vedolizumab post surgery and observations regarding TNF naïve and patients with a history of prior cancer on vedolizumab. Methods: Utilising the vedolizumab database from the IBD department, the last 4 years of data was analysed, specifically identifying those who had resectional surgery with vedolizumab post surgery for prevention of recurrence or confirmed anastamotic recurrence. Data included indications for vedolizumab and Rutgeerts scoring at the anastomosis for those who had TI surgery. Results: 81 patients' data were on the vedolizumab database and their clinical notes were audited by the IBD team. Clinical remission was achieved in 49% of patients in our cohort, with the other 51% having a loss of response, side effects or primary non responders. 37% of those whose Crohns was in remission post vedolizumab were anti-TNF naïve compared to 12% of anti-TNF naïve patients in whom vedolizumab failed. 21 out of 81 patients had surgery for Crohns disease. Clinical remission was achieved in 66% (n=14) of patients started vedolizumab post resectional surgery due to being high risk of recurrence, or a Rutgeerts score or i2 or greater. This is compared to 33% of patients(n=7) who failed vedolizumab treatment post surgery. There was no statistical difference between Rutgeerts scoring (when appropriate) in those who went into clinical remission and those who did not. On a further observational note; indications for vedolizumab differed between the patients in remission and those who had failed vedolizumab. 40% of the patients in remission had either cancer or a contraindication to an anti-TNF e.g. cardiac failure, or severe opportunistic infection on infliximab (PCP or mycobacterial infection). Only 9% of patients who failed vedolizumab treatment had cancer. Conclusions: Over 4 years, we achieved clinical remission in 49% of patients with Crohns disease using vedolizumab. 34% of these patients had had resectional surgery for their Crohns disease and were in remission. This real world data indicates that vedolizumab is a useful biological therapy in maintaining remission in patients post resectional Crohns surgery. The data also suggest, in concordance with the current literature, that being anti-TNF naïve affords a better prognosis with vedolizumab, than having failed treatment with an anti-TNF prior to vedolizumab.